Sequential methodology for the selection of sanitary landfill sites: A comparison with a traditional method - Mazzuco, Giulia G.; Souza, Natália C.; Oliveira, Vinícius G.; Gobbo, Caio A.R.; Moreira, Emerson R.; Lollo, José A. [UNESP]; Lorandi, Reinaldo; Moschini, Luiz E. (Inderscience Publishers, 2020)
A sequential methodological approach for sanitary landfill sites selection is proposed. Spatial data were processed in a GIS platform using multi-criteria decision analysis (analytic hierarchy process, boolean, fuzzy, and weighted sum). A traditional weighted sum method was compared to the sequential method proposed herein. Using weighted sum, 57.98% of the area results propitious versus 8.98% using the sequential method. Strong variation also occurs in the areas classified as restrictive, which increases from 0.60% to 26.01%. Most significant differences occurred in urban areas neighbouring and areas high slope areas with rocky outcropping substrate (strong restriction to sanitary landfills implantation). Once traditional method results average classes, areas with strong restriction for one attribute can be selected. In sequential method, the overlapping of the environmental, legal and operational attributes results more consistent classification, more conservative socio-environmental evaluation, reducing environmental impacts mitigation needs and decreasing the management risks and general enterprise costs.
Keywords: Analytic hierarchy process; Environment; Geographic information system; Hydrographic basin; Method comparison; Multi-criteria analysis; Rio Claro hydrographic basin; Sanitary landfill; Sequential methodological; Sites selection; Waste management; Weighted sum